(untitled) (Research, Society and Development, 2021)
Melatonin (N-acetyl-5-methoxytryptamine) is a hormone secreted by the pineal gland. In men, melatonin affects reproductive regulation in three main ways. First, it regulates the secretion of GnRH and LH. Second, it regulates testosterone synthesis and testicular maturation. Third, as a potent deputare of free radical that is both lipophilic and hydrophilic. The mammalian testis is an organ susceptible to environmental and therapeutic toxic agents that compromise spermatogenesis, the present study aimed to analyse the influence of constant illumination, melatonin and geldanamycin under the testis of rats treated for 60 days. Males were randomly divided into 4 groups, each consisting of 5 animals, which are: Group I - control rats (untreated); Group II - rats subjected to constant illumination for 60 days; Group III - rats subjected to constant illumination for 60 days and treated with melatonin for 60 days; Group IV - rats subjected to constant illumination for 60 days, treated with melatonin and geldanamycin for 60 days. Exposure to constant illumination affects the development of germinal epithelium, as well as decreased weight of the testicles, Leydig, Sertoli, and testosterone cells. Melatonin and geldanamycin treatment have a protective effect against constant illumination, reducing testicular damage when taken together.